2010
DOI: 10.1359/jbmr.090717
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D receptor (VDR) gene polymorphism is associated with left ventricular (LV) mass and predicts left ventricular hypertrophy (LVH) progression in end-stage renal disease (ESRD) patients

Abstract: Left ventricular hypertrophy (LVH) is a strong cardiovascular risk marker in end-stage renal disease (ESRD) patients. Vitamin D deficiency and/or disturbed vitamin D signaling has been implicated in LVH in experimental models. Because the BsmI vitamin D receptor VDR gene polymorphism may alter VDR function, we performed a cross-sectional and longitudinal study in a cohort of 182 dialysis patients to investigate (1) the relationship between BsmI VDR gene polymorphism and left ventricular mass index (LVMI) measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(60 citation statements)
references
References 27 publications
1
57
0
2
Order By: Relevance
“…Although mild-to-moderate degrees of LVH remain powerful independent predictors of survival, the causal relationship of hypertension alone to LVH in CKD remains uncertain. In fact, the data suggest other factors, including altered vitamin D metabolism, may contribute to this alteration [22,26,28,43]. PRIMO will directly test this hypothesis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Although mild-to-moderate degrees of LVH remain powerful independent predictors of survival, the causal relationship of hypertension alone to LVH in CKD remains uncertain. In fact, the data suggest other factors, including altered vitamin D metabolism, may contribute to this alteration [22,26,28,43]. PRIMO will directly test this hypothesis in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the relevant role of vitamin D in heart disease, the association between LVH and VDR gene polymorphisms has recently been investigated, and it has been reported that VDR Bsm I gene polymorphism is involved in the development of LVH in ESRD patients [47,48] and is independently related to LVH progression in dialysis patients and in stage IIIb CKD patients. The presence of the Bsm I mutated variant of the VDR gene in ESRD patients has been proposed as a novel marker of disrupted vitamin D signaling pathway, inducing an increase in the LV mass index [48].…”
Section: Pathophysiology Of Lvh In Ckd Patientsmentioning
confidence: 99%
“…VDR knockout mice exhibit increased LVMI, and human BsmI phenotype is associated with LVMI and LVMI progression (55)(56)(57).…”
Section: Altered Fgf23-klotho Expression and Vitamin D Deficiency As mentioning
confidence: 99%